ANALISIS MOM AND POP STORE DI KOTA BATAM HINGGA TAHUN 2018: ANALISIS MOM AND POP STORE DI KOTA BATAM HINGGA TAHUN 2018 - Tiurniari Purba (JURNAL AKUNTANSI BARELANG, 2019)
Non-minimarket traders and convenience stores are getting weaker along with the presence of modern retailers. Non-minimarket traders are also called traders at mom and pop or mom and pop stores. This case happened not only in other cities or other countries, but also in Batam. The presence of modern retailers, especially retail Indomaret and Alfamart retail in Batam, gave a lot of changes to the mom and pop store. This article aims specifically of analyzing the situation faced by mom and pop stores in Batam after the presence of modern retailers, especially Indomaret and Alfamart. And to what extent does the influence of the presence of Indomaret and Alfamart affect shops and stalls in Batam City? The research methodology used to analyze is a type of qualitative research with a case study approach to the type of situation analysis. The type of case study of this study is trying to analyze the situation of a particular event or event. External situation analysis is a systematic review of the background of problems that are outside the organization. Types of external situation analysis include secondary data (literature studies), surveys, observations, and content analysis. From the results of the analysis it was found that the presence of modern retailers until 2018 cannot be rejected and resisted by those who have a direct interest because access through the government of a wide open city. As a result, hundreds of modern retailers, especially Indomaret retail and Alfamart retail, have been established in Batam city. The mom and pop store has been eliminated, ranging from four to five mom and pop stores that broke up and closed in every housing complex. The hope for the mom and pop store owners that still persists up to now is the government's interference with the quota limit on the number of modern retailers. Also the involvement of the government both financially and ideas to foster the community about healthy ways to compete in the market.